(untitled) - Ralf Bleile; Berit Valentin Eriksen; Ulf Ickerodt; Wiebke Kirleis; Johannes Müller; Ulrich Müller (Offa, 2022)
Offa is named after a legendary king of the Anglo-Saxons reigning over part of Schleswig-Holstein, who was praised for his braveness and wisdom. The early volumes of Offa, which started in 1936, mainly published articles on local Archaeology, but already showing a wide chronological range from Prehistory to the Middle Ages. Archaeology being a trans-regional science, in the course of time numerous scholars from Scandinavia, Western, Central and Eastern Europe presented their results of research. Today Offa is a renowned international archaeological periodical. Before publication all contributions are peer-reviewed. The articles are published in German or English, with a short summary in both languages.